Variations of Relative Clause Translation from Indonesian to English - Tyas Gita Atibrata (Hasanuddin University, 2022)
Relative clauses are clauses that explain a noun in order to define or explain a noun further, articles, adjectives, or relative clauses are often used. In an effort to translate from the source language into the target language there is often a strategy used in translating these relative clauses. There are differences in realization in translating these relative clauses, making the researcher wanted to know on how the variations in the equivalent translation of Indonesian relative clauses into English are. There is a novel and its translation used in this research design. The novel that will be used as a source of data in this study is Bumi Manusia by Pramoedya Ananta Toer and its translation ‘The Earth of Mankind’. Data collection was carried out by listening (observing method) and noting (note-taking method) the relative clauses of data on novels in the Indonesian language as the source language and their translation into the target language. The data were then analyzed to find equivalent relative clause variants in Indonesian in English. By analysisng the data it can be found that the variations of relative clause translation from Indonesian to English are (1) relative clauses (with relative pronoun who, which, that, whose, whom), (2) adjectives, (3) present participle, (4) past participle, (5) noun phrase, (6) prepositional phrase, (7) noun class, and (8) verb.